Strategy of integrated development: Some remarks on the development of rural areas in developing countries - Karl Fasbender (Intereconomics, 1982)
The emphasis of development policies has for many years been placed on primarily growth-oriented development strategies. Although the latter have indeed induced an astounding increase in real GNP levels in Third World countries, they have not been able to decisively reduce existing social disparities. The more distribution-oriented approaches prevalent since the mid-70s have also, for their part, revealed substantial weaknesses. The strategy of integrated development attempts to combine the positive elements of both approaches into one comprehensive modus operandi.
Keywords: 330; Development Strategy